Multipotent Mesenchymal Stromal Cells: Possible Culprits in Solid Tumors? - Pascal David Johann; Ingo Müller (Hindawi Limited, 2015)
The clinical use of bone marrow derived multipotent mesenchymal stromal cells (BM-MSCs) in different settings ranging from tissue engineering to immunotherapies has prompted investigations on the properties of these cells in a variety of other tissues. Particularly the role of MSCs in solid tumors has been the subject of many experimental approaches. While a clear phenotypical distinction of tumor associated fibroblasts (TAFs) and MSCs within the tumor microenvironment is still missing, the homing of bone marrow MSCs in tumor sites has been extensively studied. Both, tumor-promoting and tumor-inhibiting effects of BM-MSCs have been described in this context. This ambiguity requires a reappraisal of the different studies and experimental methods employed. Here, we review the current literature on tumor-promoting and tumor-inhibiting effects of BM-MSCs with a particular emphasis on their interplay with components of the immune system and also highlight a potential role of MSCs as cell of origin for certain mesenchymal tumors.